ASPEK HUKUM PERJANJIAN FRANCHISE - suhaila zulkifli zulkifli (Ilmu Hukum Prima (IHP), 2018)
In Indonesia a retail sales business such as a franchise is being developed. Although the use of a franchise system in Indonesia has been rife by the business community and has been going on for quite a long time, but in the 1997 battle, there was a regulation that specifically regulates the franchise problem.That the form of a franchise agreement between the producer and the seller is in the form of a standard agreement which contains the rights and obligations that must be carried out by the parties. The legal consequences if there is a default in the franchise agreement between the producer and the seller, then the party causing the loss is obliged to provide compensation to the aggrieved party to the dispute. If in a franchise agreement a dispute occurs, it must be submitted to the Arbitration Court. The role of the court in overruling the contract from the form of franchise contract is based on article 1338 paragraph 3 of the Civil Code of the principle of good faith so that the judge is authorized to interpret the contents of the franachise agreement whether in accordance with propriety and appropriateness, in addition to binding an agreement under normal conditions, to prevent injustice.